2017
DOI: 10.17706/ijeeee.2017.7.4.255-263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fintech on the Productivity in the Taiwan Banking Industry

Abstract: Abstract:The development of financial technology has fostered a wave revolutionary change in financial service industry worldwide. The objective of this study is to examine whether the adoption of Fintech contributes to the productivity growth of the Taiwan banking industry in 2015. To investigate such potential effect, the study use the preferred Cost Malmquist Index to estimate the 25 listed sample banks over the period from 2010 to 2015. The empirical result suggests the observed period 2014-2015, the ΔPTE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Researchers have explored a wide range of topics, but there are rarely any studies about the effect of fintech and other high-tech services on the operation of the banking industry. One of the few papers that addressed this issue is by Yang et al (2017) [45], who used the cost Malmquist productivity index to estimate the effect of fintech on the banking sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have explored a wide range of topics, but there are rarely any studies about the effect of fintech and other high-tech services on the operation of the banking industry. One of the few papers that addressed this issue is by Yang et al (2017) [45], who used the cost Malmquist productivity index to estimate the effect of fintech on the banking sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, fintech is outlined as a set of activities that have the capacity to run and deliver the business in a revolutionary way. It has influenced and reshaped the business models of traditional banks (Yang et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent research has focused extensively on the efficiency analysis of financial institutions. Omrani et al (2023) as demonstrated by Yang et al (2017), Ortaköy and Özsürünç (2019), Ky et al (2019), andLiu et al (2019). Some scholars also believe that fintech has had an impact on financial transactions and services, such as Gomber et al (2018).…”
Section: Introductionmentioning
confidence: 98%
“…In dynamic DEA, Klopp (1985) first proposes window analysis, and subsequent developments include the Malmquist index by Färe et al (1994). Scholars using the Malmquist index for analysis are Ramakrishna et al (2016), Shi et al (2017), Yang et al (2017), and Mansour and Moussawi (2019). Färe and Grosskopf (1996) include inter-connecting activities in dynamic analysis, and subsequent developments appear in Park and Park (2009).…”
Section: Introductionmentioning
confidence: 99%